Implantation of Decellularized Extracellular Matrix with Resistance Training Effectively Repairs a Volumetric Muscle Loss - Lee, Kwangjun; Hong, Kwang-Seok; Park, Wonil (Exercise science (Seoul, Korea), 2022)
PURPOSE: Skeletal muscle has remarkable regenerative capacity in most minor injuries induced by mechanical laceration, overstretching, and toxins. However, volumetric muscle loss (VML) injury, a large volume of muscle loss beyond the self-repair capacity, causes functional disability and morphological deformities. This study investigated the effects of myofiber injection into a decellularized extracellular matrix (ECM) and resistance training (RT) on skeletal muscle regeneration following VML injury.METHODS: 6-months-old male Fischer CDF rats and 2-months-old F344-Tg (UBC-EGFP) rats (myofiber donors) were used in this study. Approximately 20% of the mass of the lateral gastrocnemius (LGAS) was excised and replaced by ECM of similar dimensions. Thirty myofibers were injected into the injured region seven days post-injury. Ladder climbing (RT) was allowed 10 days post-defect surgery, and the rats were subjected to ladder climbing with a weight every third day for 6 weeks.RESULTS: After 56 days of recovery and exercise training, the cross-sectional area (CSA) of intact muscle in the EXE group (5,104±92 μm2) increased significantly compared to that in the ECM (4,657±79 μm2) group. The number of blood vessels larger than 20 μm in diameter, capillaries excluded, showed a significant difference between the ECM+EXE (34.25±4.2) and ECM (21.75±3.89) groups. A significant reduction of fibrosis in the ECM+EXE (44.50±1.6%) group was observed compared to the ECM (69.25±1.9%) and ECM+FIB+EXE (63.00±1.7%) groups. Moreover, the small muscle fiber area within the transplanted ECM was significantly larger in the ECM+EXE (1.37±0.03 mm2) than in both the ECM (0.49±0.01 mm2) and ECM+FIB (0.62±0.01 mm2) groups.CONCLUSIONS: These data suggest that ECM transplantation with RT effectively repairs VML by enhancing hypertrophy, angiogenesis, and myofiber infiltration throughout the entire ECM.